2015
DOI: 10.1186/s12944-015-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dietary supplementation with saury oil attenuates metabolic abnormalities in mice fed a high-fat diet: combined beneficial effect of omega-3 fatty acids and long-chain monounsaturated fatty acids

Abstract: BackgroundPacific saury is a common dietary component in East Asia. Saury oil contains considerable levels of n-3 unsaturated fatty acids (PUFA) and long-chain monounsaturated fatty acids (LCMUFA) with aliphatic tails longer than 18 carbons. In our previous study, consumption of saury oil for 4 to 6 wk improved insulin sensitivity and the plasma lipid profile in mice. However, the long-term effects of saury oil on metabolic syndrome (MetS) risk factors remain to be demonstrated. In the current study, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…Soni et al (2015) kept the same ingredients in all groups, the only change in diet was that the obese treatment group received 20 g/kg of fish oil and 30 g/kg of corn oil, while the obese control group received 50 g/kg of corn oil [34]. keep the same amount of all nutrients in the diet of experimental groups, with the exception of an exchange of 100 g/kg of lard for 100 g/kg of saury oil [35]. Table 5.…”
Section: Lean Control Obese Control Lean Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Soni et al (2015) kept the same ingredients in all groups, the only change in diet was that the obese treatment group received 20 g/kg of fish oil and 30 g/kg of corn oil, while the obese control group received 50 g/kg of corn oil [34]. keep the same amount of all nutrients in the diet of experimental groups, with the exception of an exchange of 100 g/kg of lard for 100 g/kg of saury oil [35]. Table 5.…”
Section: Lean Control Obese Control Lean Treatmentmentioning
confidence: 99%
“…Diet Composition [29] HFD Control: Lard-based diet 49% total kcal of diet from fat HFD Treatment: 41.7% total kcal of diet from treatment oils [30] Lean Control: 45 g/1045.0 g (10% of kcal) from soybean oil and 350 g/1045.0 g of sucrose Lean Treatment: 45 g/1045.0 g (10% of kcal) from pine nut oil and 350 g/1045.0 g of sucrose HFD Control: 157.5 g/848.1 g of lard (35% of kcal), 45 g/848.1 g (10% of kcal) from soybean oil and 172.8 g/848.1 g of sucrose HFD Treatment: 157.5 g/848.1 g of lard (35% of kcal), 45 g/848.1 g (10% of kcal) from pine nut oil and 172.8 g/848.1 g of sucrose [31] Lean Control: 40 g/kg of soybean oil, 100 g/kg of sucrose and 140 g/kg of casein Lean Treatment: 36 g/kg of fish oil, 4 g/kg of soybean oil, 100 g/kg of sucrose and 140 g/kg of casein HFD Control: 238 g/kg of lard, 40 g/kg of soybean oil, 100 g/kg of sucrose and 175 g/kg of casein HFD Treatment: 238 g/kg of fish oil, 40 g/kg of soybean oil, 100 g/kg of sucrose and 175 g/kg of casein [32] Lean Control: 42 g/kg of soybean oil, 622.69 g/kg of cornstarch, 100 g/kg of sucrose, 42 g/kg of soybean oil and 136 g/kg of casein HFD Control: 236 g/kg of lard, 42 g/kg of soybean oil, 352.192 g/kg of cornstarch, 100 g/kg of sucrose, 42 g/kg of soybean oil and 170 g/kg of casein HFD + 25% MCT: 177 g/kg of lard, 42 g/kg of soybean oil, 61.5 g/kg of medium-chain triacylglycerol, 350.192 g/kg of cornstarch, 100 g/kg of sucrose, and 170 g/kg of casein HFD + 75% MCT: 59 g/kg of lard, 42 g/kg of soybean oil, 184,5 g/kg of medium-chain triacylglycerol, 345.192 g/kg of cornstarch, 100 g/kg of sucrose, and 170 g/kg of casein HFD + 100% MCT: 42 g/kg of soybean oil, 246 g/kg of medium-chain triacylglycerol, 342.692 g/kg of cornstarch, 100 g/kg of sucrose, and 170 g/kg of casein [33] HFD Control: 200 g/kg of lard, 200 g/kg of casein, 250 g/kg of corn starch, 100 g/kg of fructose, 100 g/kg of sucrose, and 50 g/kg of soybean oil HFD + 2% of Starfish Oil: 180 g/kg of lard, 200 g/kg of casein, 250 g/kg of corn starch, 100 g/kg of fructose, 100 g/kg of sucrose, 20 g/kg of starfish oil and 50 g/kg of soybean oil HFD + 5% of Starfish Oil: 150 g/kg of lard, 200 g/kg of casein, 250 g/kg of corn starch, 100 g/kg of fructose, 100 g/kg of sucrose, 50 g/kg of starfish and 50 g/kg of soybean oil [34] Lean Control: 222 g/kg of casein, 50 g/kg of sucrose, 560 g/kg of corn starch, 50 g/kg of cellulose, 25 g/kg of corn oil and 25 g/kg of coconut oil HFD Corn Oil Control: 256 g/kg of casein, 100 g/kg of sucrose, 348 g/kg of corn starch, 58 g/kg of cellulose, 100 g/kg of coconut oil and 50 g/kg of corn oil HFD Treatments: 256 g/kg of casein, 100 g/kg of sucrose, 348 g/kg of corn starch, 58 g/kg of cellulose, 100 g/kg of coconut oil, 30 g/kg of corn oil + 20 g/100 g of EPA and DHA-enriched oils [35] HFD Control: 258 g/kg of casein, 162 g/kg of maltodextrin, 89 g/kg of sucrose, 65 g/kg of cellulose, 320 g/kg of lard, and 32 g/kg of soybean oil HFD Treatment: 258 g/kg of casein, 162 g/kg of maltodextrin, 89 g/kg of sucrose, 65 g/kg of cellulose, 220 g/kg of lard, 32 g/kg of soybean oil and 100 g/kg of saury oil [36] HFD…”
Section: Refmentioning
confidence: 99%
“…Although earlier animal studies showed that diets enriched in the LCMUFA isomer C22:1 caused a transient lipidosis in some organs, lipidosis disappeared upon continued feeding, possibly due to increased activity of peroxisomal β-oxidation [27]. A recent animal feeding study from our group showed that the LCMUFA-rich diet resulted in a small but significant increase in each LCMUFA isomer in plasma and vital organs, such as liver, skeleton muscle, and duodenum, with the most prominent changes occurring in adipose tissues [28]. Similarly, generally MUFA is also enriched in adipose tissue [29], because of either its greater entrance into adipocytes or because of a putative desaturation process of saturated FA by the steraoyl desaturase (SCD1).…”
Section: Incorporation Of Lcmufa Into Plasma and Organ Lipidsmentioning
confidence: 99%
“…1. For example, a high-fat fed C57BL/6J mice treated with saury oil for either short term (6-weeks) or long term (18-weeks) showed major improvements in several features related to metabolic syndrome [28, 34]. A 10% ( w/w ) of supplementation of saury oil (equivalent to appropriate 3.5% ( w/w ) LCMUFA) in a high-fat diet ameliorated diet-induced hyperinsulinemia and dyslipidemia compared to high-fat control diet.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation